2005
DOI: 10.1093/aob/mci217
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analysis of Transcript Abundance and Translation in Arabidopsis Seedlings Subjected to Oxygen Deprivation

Abstract: Alterations in transcript abundance and translation contribute to the differential regulation of gene expression in response to oxygen deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
170
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(193 citation statements)
references
References 46 publications
10
170
0
4
Order By: Relevance
“…For example, Arabidopsis protoplasts that are not well aerated demonstrate large reductions in accumulation of many gene transcripts, especially those coding for energy consuming processes such as ribosome biogenesis and anabolism (Baena-González et al 2007). Furthermore, in Arabidopsis seedlings a large portion (70%) of cellular mRNA's become poorly translated upon low O 2 stress (Branco-Price et al 2005, 2008. Even in highly-tolerant species with relatively high rates of ethanolic fermentation supporting anoxic shoot elongation (e.g.…”
Section: Submergence -Short Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Arabidopsis protoplasts that are not well aerated demonstrate large reductions in accumulation of many gene transcripts, especially those coding for energy consuming processes such as ribosome biogenesis and anabolism (Baena-González et al 2007). Furthermore, in Arabidopsis seedlings a large portion (70%) of cellular mRNA's become poorly translated upon low O 2 stress (Branco-Price et al 2005, 2008. Even in highly-tolerant species with relatively high rates of ethanolic fermentation supporting anoxic shoot elongation (e.g.…”
Section: Submergence -Short Durationmentioning
confidence: 99%
“…Examples are the use of pyrophosphate (PP i ) over ATP as a high-energy donor (Huang et al 2008) and the preferred use of sucrose synthase (SuSy) and UDPglucose pyrophosphorylase for the degradation of sucrose (Geigenberger 2003). More generally, certain mRNAs circumvent translational repression and/or are transcriptionally upregulated thus selectively ensuring production of a specific set of proteins (Branco-Price et al 2005, 2008. These 'anaerobic Fig.…”
Section: Submergence -Short Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, evidence suggests that r-protein regulation occurs predominantly post-transcriptionally, via partitioning of r-protein transcripts in either the polysomal (actively translated) or RNP (inactive) fractions. For example, in response to sucrose starvation (Nicolai et al 2006), drought (Kawaguchi et al 2004), or hypoxia (Branco-Price et al 2005), r-protein transcripts exhibit a coordinated decrease in polysomal loading. Nevertheless, transcriptional regulation is also important given Wndings that r-protein transcripts from a number of plant species show their greatest accumulation in mitotically active tissues and are coordinately upregulated following wounding and phytohormone treatments (reviewed in McIntosh and Bonham-Smith 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The end products from in vitro translation of polysomes also reflect the activity of mRNAs that respond to stress [43]. Synthesis of most proteins under environmental stresses is reduced but translation of individual mRNA species is differentially regulated [23,[44][45][46]. Kawaguchi et al [45] showed that less than 1% of the stress-induced mRNAs increased significantly in polysome association, what can suggest that proteins encoded by this mRNAs were synthesized at higher levels during stress conditions.…”
Section: Discussionmentioning
confidence: 99%